2021
DOI: 10.1007/s42001-021-00118-8
|View full text |Cite
|
Sign up to set email alerts
|

Digital media and misinformation: An outlook on multidisciplinary strategies against manipulation

Abstract: This review discusses the dynamic mechanisms of misinformation creation and spreading used in social networks. It includes: (1) a conceptualization of misinformation and related terms, such as rumors and disinformation; (2) an analysis of the cognitive vulnerabilities that hinder the correction of the effects of an inaccurate narrative already assimilated; and (3) an interdisciplinary discussion on different strategies for coping with misinformation. The discussion encompasses journalistic, educational, govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 90 publications
(115 reference statements)
0
16
0
2
Order By: Relevance
“…Examining the determinants described above, several types of interventions can be implemented to limit the spread of fake news and prevent people from believing it. A recent review [7] identified five main approaches to counter misinformation ( Table 2 ). Examples of these approaches have already been mentioned, such as media education, social-media warnings or critical thinking skills.…”
Section: Implications For Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the determinants described above, several types of interventions can be implemented to limit the spread of fake news and prevent people from believing it. A recent review [7] identified five main approaches to counter misinformation ( Table 2 ). Examples of these approaches have already been mentioned, such as media education, social-media warnings or critical thinking skills.…”
Section: Implications For Preventionmentioning
confidence: 99%
“…Research into fake news has progressed exponentially in the last 5 years ( Box 1 ) [4] , [5] , [6] , [7] . Hence, this update addresses only a part of the fake news-related issues and focuses on the reasons leading individuals to believe fake news, noting that rheumatology is scarcely represented.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is a wealth of evidence in rumor psychology to support that increased exposure afforded to disinformation, even if successful in discrediting, can mean inaccurate beliefs “still tend to persist, but in a weakened state” ( 29 ). In other words, so long as the QAnon beliefs or conspiracies are commented upon, they have the potential to gain traction and be integrated within the audience's mental models regarding human trafficking as well as our sociopolitical climate ( 30 ).…”
Section: Mechanisms Of Disinformationmentioning
confidence: 99%
“…En s’appuyant sur les déterminants décrits plus haut, plusieurs types d’interventions peuvent être mis en place afin de limiter la propagation des fake news et empêcher les individus d’y croire. Une récente revue [7] a identifié cinq stratégies permettant de lutter contre la mésinformation ( Tableau 2 ). Quelques-unes de ces stratégies ont déjà été mentionnées, comme l’éducation aux médias, la présence de message de mises en garde sur les médias sociaux ou la promotion de la pensée critique.…”
Section: Implications Pour La Préventionunclassified
“…La recherche sur les fake news a connu une forte progression au cours de ces 5 dernières années ( Encadré 1 ) [4] , [5] , [6] , [7] . Cette mise à jour n’aborde qu’une partie de la problématique des fake news et met l’accent sur les raisons qui motivent la croyance aux fake news ; à noter que la rhumatologie est peu représentée.…”
Section: Introductionunclassified